Trajectory Synthesis of Aircraft Cabin Door Lifting Mechanism Based on the Homotopy Continuation Method - Peng Jiyou; Hang Lubin; Liu Anxin; Wu Borui; Huang Xiaobo; Wu Yang (Jixie chuandong)
The aircraft cabin door is a passage channel of the cabin. The center line of the fuselage guide groove shall coincide with the movement track of the guide wheel at the end of the lifting mechanism, ensuring the reliable opening/locking of the cabin door. Based on the ordered single open chain method, the trajectory synthesis kinematic equations of two single open chain units of the lifting mechanism are established; the variables of the equations are grouped into homogeneous groups and the Bezout number is only 320, which reduce the homotopy tracking path; by constructing the initial equations and solving the homotopy equations, six sets of non-negative real number configuration solutions of rod length are obtained, and the corresponding configuration of single open chain element combination is drawn. Based on the motion space of the mechanism and the force transmission efficiency of the lifting mechanism, the door lifting mechanism to realize the movement of the aircraft door according to the desired trajectory is obtained.